Análisis de los mecanismos de ensamble en tiendas de acampar de media montaña - Shinin Tubon, Bryan Gonzalo (2025)
This theoretical research analyses the assembly mechanisms used in mid-mountain camping tents, evaluating their functionality, efficiency and adaptability to demanding weather conditions. In a context of increasing demand for specialized camping equipment, this study contributes to the academic and practical knowledge on the systems that make up the mechanism and facilitate assembly in high altitude environments, characterized by strong winds, low temperatures and uneven terrain. The importance of designing intuitive, light and resistant mechanisms that provide a pleasant user experience and meet the specific requirements of mid-mountain is highlighted. In addition, the study identifies the mechanism and system together with its assembly components that offer the best feasibility, optimizing the time and effort of the camper, ensuring a resistant temporary shelter. It also offers a theoretical framework of reference for designers and manufacturers interested in improving the assembly technology in camping tents. Finally, the development of more competitive and functional products is promoted, encouraging people's contact with nature through outdoor activities such as camping.